Benzoxazole derivatives as new VEGFR-2 inhibitors and apoptosis inducers: design, synthesis, in silico studies, and antiproliferative evaluation - Mohammed S. Taghour; Hazem A. Mahdy; Maher H. Gomaa; Ahmed Aglan; Mahmoud Gomaa Eldeib; Alaa Elwan; Mohammed A. Dahab; Eslam B. Elkaeed; Aisha A. Alsfouk; Mohamed M. Khalifa; Ibrahim H. Eissa; Hazem Elkady (Journal of Enzyme Inhibition and Medicinal Chemistry)
In this study, a set of novel benzoxazole derivatives were designed, synthesised, and biologically evaluated as potential VEGFR-2 inhibitors. Five compounds (12d, 12f, 12i, 12l, and 13a) displayed high growth inhibitory activities against HepG2 and MCF-7 cell lines and were further investigated for their VEGFR-2 inhibitory activities. The most potent anti-proliferative member 12 l (IC50 = 10.50 μM and 15.21 μM against HepG2 and MCF-7, respectively) had the most promising VEGFR-2 inhibitory activity (IC50 = 97.38 nM). A further biological evaluation revealed that compound 12l could arrest the HepG2 cell growth mainly at the Pre-G1 and G1 phases. Furthermore, compound 12l could induce apoptosis in HepG2 cells by 35.13%. likely, compound 12l exhibited a significant elevation in caspase-3 level (2.98-fold) and BAX (3.40-fold), and a significant reduction in Bcl-2 level (2.12-fold). Finally, docking studies indicated that 12l exhibited interactions with the key amino acids in a similar way to sorafenib.